Global analysis on a class of multi-group SEIR model with latency and relapse - Jinliang Wang; Hongying Shu (Mathematical Biosciences and Engineering)
In this paper, we investigate the global dynamics of a multi-group SEIR epidemic model,allowing heterogeneity of the host population, delay in latency and delay due torelapsedistribution for the human population.Our results indicate that when certain restrictions on nonlinear growth rate and incidence are fulfilled, the basic reproduction number $\mathfrak{R}_0$ plays the key role of a global threshold parameter in the sense that the long-time behaviors of the model depend only on $\mathfrak{R}_0$. The proofs of the main results utilize the persistence theory indynamical systems, Lyapunov functionals guided by graph-theoretical approach.